POLITIK HUKUM PENGATURAN PERLINDUNGAN PEKERJA RUMAH TANGGA DI INDONESIA DALAM PERSPEKTIF HAK ASASI MANUSIA - Hanny Friska Salsabilla; Emilda Firdaus; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Domestic workers as informal workers need the same special attention and protection asformal workers. The Manpower Law cannot be used as protection because domestic workersare considered informal workers. Where the protection in question is in the form of a balance ofrights and obligations between the Domestic Worker and the employer, as well as guarantees ofsafety to achieve decent work for Domestic Workers. Indonesia is a country that upholds theprotection of human rights, by protecting the value of dignity as a whole human being. However,until now Indonesia does not yet have comprehensive regulations governing the protection ofdomestic workers. The objectives of this thesis research are first, legal politics regulating theprotection of domestic workers in Indonesia from a human rights perspective. Second, the idealconcept of regulating the protection of domestic workers in Indonesia from a human rightsperspective.This study was structured using qualitative analysis. Qualitative analysis producesdescriptive data, namely collecting all the necessary data obtained from primary and secondarylegal materials. This type of research is normative juridical, namely research that is focused onexamining the application of rules or norms in positive law.The results of the research conducted by the author are, first, domestic workers incarrying out their work are considered vulnerable to various problems, this of course makesprotection of domestic workers very necessary. Therefore, the existence of the Law on theProtection of Domestic Workers does not only provide protection for domestic workers, but alsoprovides equal protection for employers, especially regarding the balance of rights andobligations between domestic workers and employers. Second, the ideal concept of regulatingthe protection of domestic workers in Indonesia from a human rights perspective, namely makingchanges to the labor law; expediting the ratification of the Domestic Workers Bill and makingadditions to content material; evaluate and make changes to the substance of the PermenakerPPRT when the Domestic Workers Bill has been passed so that there is no confusion; Indonesiacan participate in ratifying ILO Convention 189 to become a strong reason for the ratification ofthe Domestic Workers Bill.Keywords: Legal Politics- Domestic Workers- Human Rights